EV+A 2002 : heroes + holies. - Limerick City Gallery of Art; Exhibition Visual + Art Limerick 2002; Byrne, Kate; Cai Guo-Qiang; Canevari, Paolo; Canning, Michael; Carlsson, Gabriella; Chandrasekaran; Charlesworth, Ian; Coe, Tim; Dadi, Iftikhar & Elizabeth; Dono, Deri; et al. (Oysterhaven : Gandon Editions, 2002)
Abramovic, Marina ; Araki, Nobuyoshi ; Bourke, David ; Byrne, Kate ; Cai Guo-Qiang ; Campion, John ; Canevari, Paolo ; Carlsson, Gabriella ; Chandrasekaran ; Charlesworth, Ian ; Cherrier, Martial ; Coe, Tim ; Coogan, Amanda ; Dadi, Elizabeth ; Dadi, Ittikhar ; Dono, Heri ; Duggan, Andrew ; Dunhill & O'Brien ; Dunne, David ; Earley, Brendan ; Elliott, Neva ; Farrell, Des ; Fitzgerald, Tom ; Healy, Martin ; Iremonger, Sarah ; Jaarsma, Mella ; Jeong-Hwa, Choi ; Johansson, Peter ; Joyce, Garreth ; Kazma, Ömer Ali ; Keena, Pauline ; Kelly, Aileen ; Kelly, Anthony-Noël ; Kenny, Sarah ; Kheirkhah, Maria ; Killane, Helen ; Kramer, Arno ; Kumjim, Prapon Joe ; Laherty, Bernie ; Lin Tian-miao ; Ludmann, Karin ; Lynch, Breda ; MacWilliam, Susan ; Mathews, John ; McCann, Niamh ; McCrum, Philip ; Monk, Meredith ; Morgan, Peter ; Murphy, Clive ; Nolan, Collette ; O'Doherty, Ciarán ; O'Kane, Eamon ; O'Reilly, Vanessa ; O'Riordan, Amy ; O'Sullivan, Yvonne ; Ouch!Electro ; Rasdjarmrearnsook, Araya ; Rekula, Heli ; Rodland, Torbjorn ; Sharkey, Ronan ; Shawanasai, Michael ; Sitthiket, Vasan ; Slockett, Catherine ; Smyth, Bernard
curator : Apinan Poshyananda (Thailand). The city of Limerick has opened up galleries, exhibition places, churches, pubs, shop windows, streets, façades, parks and the River Shannon to the presence of EV+A 2002.
ev+a adjudicators, 1977-2002 p. 201
ev+a awards, 1977-2002 p. 202-203
ev+a lectures 2002 p. 200
ev+a story p. 205-207
Engels
EV+A 2002 : heroes + holies, Limerick City Gallery of Art Limerick, 16.03 - 09.06.2002
Keywords: Ierland